2023
DOI: 10.1002/fes3.504
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering agricultural credits and agricultural production nexus from a global perspective

Dicle Ozdemir

Abstract: Access to credit has been a key component in protecting a country's agriculture sector against uncertainties and climate‐related shocks. Agricultural credits may also increase both agribusiness sectors' and farming‐related commercial activities' exposure to world markets. This study aims to investigate agricultural credits' short‐run and long‐run effects on agricultural production using control variables such as foreign direct investments, inflation rate, and government expenditures. We found that credits to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…, 2021; Shikur, 2023; Osabohien et al. , 2022; Ozdemir, 2024; Chandio et al. , 2020b; Islam, 2020; He et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021; Shikur, 2023; Osabohien et al. , 2022; Ozdemir, 2024; Chandio et al. , 2020b; Islam, 2020; He et al.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors (Simionescu et al, 2021;Chandio et al, 2022a, b) suggested that domestic credit to the private sector played a significant role in boosting agricultural production. At the same time, some authors (Temas et al, 2021;Shikur, 2023;Osabohien et al, 2022;Ozdemir, 2024;Chandio et al, 2020b;Islam, 2020;He et al, 2022) suggested that institutional credit for agriculture positively affected agricultural production. Several previous scholars also incorporated fertilizer consumption (Nasrullah et al, 2021;Ali et al, 2022;Gul et al, 2022;Rizwanullah et al, 2023) and pesticide consumption (Ali et al, 2022;Hossain et al, 2022;Rizwanullah et al, 2023) into their models.…”
Section: Datamentioning
confidence: 99%